Polyvinyl alcohol: a high-resolution hydrogel resist for humidity-sensitive micro-/nanostructure. (24th July 2020) - Zhang, Jian; Huang, Chao; Chen, Yingxin; Wang, Hu; Gong, Zhongmiao; Chen, Weiqian; Ge, Haixiong; Hu, Xin; Zhang, Xuefeng
Abstract: A high-resolution nanopatterning technique is desirable with the present rapid development of hydrogel nanodevices. Here, we demonstrate that polyvinyl alcohol (PVA), a popular polymeric hydrogel, can function as the negative-tone resist for electron beam lithography (EBL) with a resolution capability as narrow as 50 nm half-pitch. Furthermore, the hydrophilic groups of PVA are stable after EBL exposure, and thus the pattern still shows rapid responsivity to humidity change. An aqueous nanopatterning process including dissolution, spin-coating and development is setup, which is friendly for organic device fabrication free of organic solvent. This high-resolution nanopatterning technique with PVA is helpful for the design and realization of hydrogel-related nanodevices in the future.